2001
DOI: 10.1152/physrev.2001.81.2.807
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Mitogen-Activated Protein Kinase Signal Transduction Pathways Activated by Stress and Inflammation

Abstract: The molecular details of mammalian stress-activated signal transduction pathways have only begun to be dissected. This, despite the fact that the impact of these pathways on the pathology of chronic inflammation, heart disease, stroke, the debilitating effects of diabetes mellitus, and the side effects of cancer therapy, not to mention embryonic development, innate and acquired immunity, is profound. Cardiovascular disease and diabetes alone represent the most significant health care problems in the developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
2,660
4
34

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,047 publications
(2,751 citation statements)
references
References 365 publications
(918 reference statements)
53
2,660
4
34
Order By: Relevance
“…Activation of JNK regulates activator protein-1 (AP-1) transcription in response to environmental stress such as UV radiation [48]. Increased AP-1 activity has been implicated in inflammation, metastasis and angiogenesis, and also in the promotion and progression of various types of cancers [49][50][51]. Therefore, higher levels of ERK1/2, JNK and p38 activation may promote skin diseases in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of JNK regulates activator protein-1 (AP-1) transcription in response to environmental stress such as UV radiation [48]. Increased AP-1 activity has been implicated in inflammation, metastasis and angiogenesis, and also in the promotion and progression of various types of cancers [49][50][51]. Therefore, higher levels of ERK1/2, JNK and p38 activation may promote skin diseases in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the ERK1/2 and PI3-K/Akt signaling pathways in controlling apoptosis is well known [reviewed in 39,40], and it has been shown that ERK1/2 or PI3-K/Akt activation can confer resistance to ligands of the TNF superfamily [41,42]. Moreover, it has been reported that cells constitutively expressing HSV-2 R1 exhibit activation of the ERK1/2 signaling pathway [43] and that such activation could be involved in HSV-2 R1 antiapoptotic activity [22].…”
Section: Erk1/2 and Aktmentioning
confidence: 99%
“…Among these are mitogen-activated protein kinases (MAPKs), which represent a central converge point regulating cellular behaviour. The three most-characterized MAPK pathways are the extracellular signal regulated kinases (ERKs), the c-Jun N-terminal kinases (JNKs) and the p38s (Kyriakis and Avruch, 2001;Wang, 2007).…”
Section: Introductionmentioning
confidence: 99%